(untitled) (Medical Forum Monthly, 2023)
Objective: To assess the clinical improvement of herniated lumbar disc after spontaneous partial or complete absorption. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the department of Orthopaedic surgery Mardan Medical Complex from December 2021 to December 2022. Materials and Methods: By employing the visual analogue scale (VAS), the intensity of the sciatic pain was evaluated at first visit and again during the follow-up. At both the first appointment and the follow-up, the herniated disc size was measured in MRI images. Follow up of all the patients was done for a period of 12 months. All the data analysis was done by employing IBM SPSS version 24. Results: In the current study, totally 40 patients were enrolled. There were 24 (60%) male participants while female participants were 16 (40%). On the first follow up after two weeks, improvement in sciatic pain was observed in 15 (37.5%) based on VAS. On second follow up after one month, improvement in sciatic pain was observed in 22 (55%) patients, after two month in 32 (80%) patients, after 4 months in 32 (80%) patients while after 6 months and after one it was improved in 38 (95%) patients. Based on disc absorption, Complete >80% disc absorption was observed in 20 (50%) patients, Partial 20-80% disc absorption was observed in 5 (12.5%) while no No change<20% disc absorption was observed in 15 (37.%) patients. Conclusion: According to the findings of our investigation, spontaneous regression may occur in cases with herniated intervertebral discs. For at least two months, conservative therapy may be considered in all patients, including those with moderate neurologic impairments.